KAJIAN HUKUM PERJANJIAN PERKAWINAN DI KALANGAN WNI ISLAM (STUDI DI KOTA MEDAN) - NOVI FAJAR ANGGRAINI (PREMISE LAW JURNAL, 2016)
It organizes marriage property, either the property brought to a marriage by either side or joint property so that it can make legal certainty in controlling and utilizing it in the married life and in the post-divorce. The problems of the research were as follows: how about the regulation on making marriage contract based on the prevailing legal provisions, the Islamic point of view on a marriage contract made by the Islamic Indonesian citizens, and the practice in marriage contracts among the Islamic Indonesian citizens in Medan. The research used judicial normative and descriptive analytic methods in order to analyze the prevailing regulations in marriage such as Law No. 1/1974, Compilation of the Islamic Law (KHI), based on the Qur’an and Hadists. The data were gathered by conducting interviews with the Islamic married couples, the Islamic scholars, judges, and notaries in Medan who had the capability of being informants and source persons. The result of the research showed that the regulation on marriage contract is stipulated in Article 29 of Law No. 1/1974 on Marriage, Article 47 until Article 52 of KHI (Compilation of the Islamic Law), and Article 139 until Article 154 of the Civil Code. The Islamic law does not explicitly regulate marriage contract. Besides that, there is no single verse in the Quran and Hadists which forbids someone to make a marriage contract as long as it is not contrary to the Islamic doctrine and it gives the benefit to the married couples. Keywords : Marriage Contract, Islamic Indonesian Citizen, Medan